Menjaga Keseimbangan Imun Jasmani dan Rohani pada Masa Pandemi Covid-19 di Desa Batuan - I Wayan Sukarma (UNHI Press, 2021)
The Covid-19 pandemic has broad implications for people's lives in Batuan Village and creates a paradoxical situation. Physical and social restrictions to minimize the risk of epidemic transmission have an impact on the obstruction of various productive activities of the community. This situation emphasizes the importance of maintaining a balance of physical and spiritual immunity so that people can avoid epidemics as well as the negative impacts they cause. The Real Work Lecture Activity - Community Service in Batuan Village indicates a strategic effort to maintain the balance of the community's physical and spiritual immunity. Physical immune strengthening is pursued through various activities to support the implementation of health protocols. Meanwhile, the strengthening of spiritual immunity is manifested by activities to increase the sraddha and devotional service of Hindus. The balance of physical and spiritual immunity is built by creating harmony between humans, the environment, and God